Bottom gate thin-film transistors using parallelly lateral ZnO nanorods grown by hydrothermal method. (15th November 2020) - Lee, Hsin-Ying; Cheng, Chun-Yang; Lee, Ching-Ting
Abstract: The 200-nm-thick aluminum zinc oxide (AZO) seed sidewall and the 1-μm-wide strips sandwiched by 3-μm-wide SiO2 barriers were utilized to grow parallelly lateral ZnO nanorods using hydrothermal method. The resulting ZnO nanorods were used for fabricating thin-film transistors. To dodge the problem of oxygen vacancies and defects resided in the ZnO nanorods, the annealing process at various temperatures was carried out. Using the measurement of photoluminescence spectra, it was estimated that the ZnO nanorods annealed in an oxygen ambience at 300 °C for 10 min had the lowest density of oxygen vacancies and defects. Consequently, its resulting thin-film transistors revealed the best performances of threshold voltage of 0.07 V, effective field-effect mobility of 63.26 cm 2 /V-s, transconductance of 20.1 μS and subthreshold swing of 0.44 V/dec. Highlights: The parallelly lateral ZnO nanorods were grown using hydrothermal method. The lowest defect density was obtained as ZnO nanorod annealed at 300 °C for 10 min. Parallelly lateral ZnO nanorods were used for fabricating thin-film transistors. 4. The best performance of TFT was VT of 0.07 V, μFE of 63.26 cm2/V-s, gm of 20.1 μS.